TANTANGAN PENDIDIKAN ISLAM DI ERA DIGITAL PERSPEKTIF PENDIDIKAN ISLAM KONTEMPORER - Umraniah; Husni, Muhammad (Dirasat: Journal Islamic Studies, 2026)
This study aims to examine the challenges of Islamic education in the digital age through the perspective of contemporary Islamic education. Using a literature review method, the article identifies key problematic issues such as curriculum dualism, moral disorientation among the younger generation, and technological adaptation barriers within educational institutions. The analysis reveals that these challenges necessitate strategic responses in the form of integrating religious and general sciences within a monotheistic (tawhid) framework, transforming interactive digital pedagogy, and strengthening holistic educator competencies. The research findings emphasize that contemporary Islamic education must balance technological advancement with the preservation of akhlaqul karimah (noble character) values to produce a generation that is globally competitive yet retains a solid religious identity. In conclusion, the synergy between adaptive policies and professional human resource management is the primary key to the sustainability of Islamic education as an instrument for cultivating insan kamil (the perfect human) in the present era.